Potensi Kerjasama Bilateral Indonesia Bangladesh Dalam Kerangka Preferential Trade Agreement - Deky Paryadi (Cendekia Niaga, 2020)
Currently, Indonesia is initiating trade cooperation between Indonesia and Bangladesh PTA. This trade cooperation is to increase Indonesia's exports to non-traditional markets. For that, it is a necessary overview of trade between Indonesia and Bangladesh to determine the market potential products Indonesia Bangladesh. From the simulation results of the Trade Complementary Index (TCI), Indonesian products for the last 2 years (2017-2018), it can be seen that Indonesian export products can meet the demands of the Bangladesh import market and it can be assumed that the people of Bangladesh have been able to receive products from Indonesia. From the simulation results of potential products, 283 tariff lines can be used as an indication of potential Indonesian request to initiate cooperation between Indonesia and Bangladesh this PTA.